Aplikasi Data Penerima Bansos Program Keluarga Harapan (PKH) Berbasis Website - Maria Claudia Letsoin; Gunawan Prayitno; Kristia Yuliawan (STMIK Pesat Nabire, 2023)
Technological developments today are increasingly more sophisticated, the usage of one of the system technologies is a feature of a computer application. The service and performance of operators in inputting Social assistance data for the family hope program Social Welfare office of Nabire Regency affects the welfare of the people within the area itself. with the aid of using present computer technology, inputting records can be made easier through making it into an application. This web-based application aims to be able to offer facilities such as inputting data that is quite fast than before. web-based applications are one of the satisfactory convenience features that can be used these days, which is an element of this system's performance, particularly the internet, which can be easily accessed by everyone online in order that it truely saves time. With this in thoughts, the design of the application Product